1979
DOI: 10.1021/j100479a007
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave study of collisional energy transfer in the dissociation of nitrogen dioxide, nitrosyl chloride, ozone, and nitrous oxide

Abstract: The thermal dissociation of N02, CINO, 03, and N20 in the low pressure range was studied in shock wave experiments. The measurements were made by using the different bath gases He, Ne, Ar, Kr, Xe, N2, 02, C02, CF4, and SF6. The results show that at high temperatures all of these gases, M, become "weak" colliders, i.e., their collision efficiencies dc(M) < 1. Comparison of relative collision efficiencies shows that dc(He)/dc(Ar) is smaller than one at low temperatures and larger than one at high temperatures. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Endo et al [34] reported the close rates within ±20% to the above for N 2 , O 2 , and He bath gases at 800 K, and assigned a factor of 3.6 for CO 2 bath gas. However, there was no bath gas dependence assumed in our study.…”
Section: Model Calculationmentioning
confidence: 59%
“…Endo et al [34] reported the close rates within ±20% to the above for N 2 , O 2 , and He bath gases at 800 K, and assigned a factor of 3.6 for CO 2 bath gas. However, there was no bath gas dependence assumed in our study.…”
Section: Model Calculationmentioning
confidence: 59%
“…It should be noted that the N 2 0 and O-atom measurements were made in separate studies (Dean, 1976, andDean andSteiner, 1977, respectively). Rate constant data for NzO + M ---> N z + 0 + M. Monat et al (1977) 14.15 0 25810 1810-3360 Ar, Kr, N2 Roth and Just (1977) 15.16 0 1500-2250 Ar Endo et al (1979) 14.59 0 28870 1700-2400 Ara Sulzmann et al (1980) 14 conclusions of the work. Rate constant data for NzO + M ---> N z + 0 + M. Monat et al (1977) 14.15 0 25810 1810-3360 Ar, Kr, N2 Roth and Just (1977) 15.16 0 1500-2250 Ar Endo et al (1979) 14.59 0 28870 1700-2400 Ara Sulzmann et al (1980) 14 conclusions of the work.…”
mentioning
confidence: 81%
“…A major problem is estimation of the weak collision factor Quack and Troe, 1977a;Tardy and Rabinovitch, 1977;Endo, Glanzer, and Troe, 1979). This quantity can be related to the average energy transferred per collision <AE) by Pc '" -<AE) Gilbert, Luther, and Troe, 1983.)…”
Section: Low-pressure Rate Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with experimental data for OCS dissociation in Ar bath gas 38 shows that β c decreases from 0.058 at 2000 K to 0.024 at 3000 K. The corresponding average energy transferred per collision − E is derived via the relation For N 2 O in an N 2 bath gas, Endo et al derived β c = 0.043 and 0.023 at 900 and 2000 K, respectively, and thus − E = 0.44 and 0.54 kJ mol −1 . 39 They also suggested that N 2 was a slightly more efficient collider than Ar, by factors of 1.26 and 1.05 at 900 and 2000 K. We therefore expect that the collision efficiency for OCS in N 2 is likely to be similar to that for Ar (in the context of the other uncertainties involved).…”
mentioning
confidence: 89%